Fatigue and recovery after high-intensity exercise Part II: Recovery interventions - Lattier, G.; Millet, G. Y.; Martin, A.; Martin, V. (International Journal of Sports Medicine, 2004)
The purpose of this study was to determine the effect of three types of recovery intervention to neuromuscular function after high-intensity uphill running exercise. The 20-min recovery interventions were (i) passive, (ii) active (running at 50 % of maximal aerobic speed), and (iii) low-frequency electromyostimulation. Evoked twitch and maximal voluntary contractions of knee extensor muscles (KE) and EMG of the vastus lateralis and vastus medialis were analysed immediately after the exercise, 10 min after the end of the recovery periods, and 65 min after the exercise (Post65). An all-out running test was also performed 80 min after the end of the fatiguing exercise. No significant differences were noted in any measured parameters but a tendency to a better performance during the all-out test was found after the electromyostimulation intervention (297.5 +/- 152.4 s vs. 253.6 +/- 117.1 s and 260.3 +/- 105.8 s after active and passive recovery, p = 0.13 and p = 0.12, respectively). At Post65, isometric maximal voluntary contraction torque did not return to the pre-exercise values (279.7 +/- 86.5 vs. 298.7 +/- 92.6 Nm, respectively; p < 0.05). During recovery, electrically evoked twitch was characterized by an increase of peak torque, maximal rate of force development and relaxation (+ 24 - 33 %; p < 0.001) but these values were still lower at Post65 than pre-exercise. Amplitude and surface of the M-wave decreased during recovery. These results show that the recovery of the voluntary force-generating capacity of KE after an intermittent high-intensity uphill running exercise do not depend on the type of recovery intervention tested here. It can also be concluded that the recovery of twitch contractile properties does not necessarily follow that of maximal muscle strength.